Integer Linear Programming Sebagai Model Alternatif Penjadwalan Ruang Kuliah di Fakultas Teknik Universitas Pattimura Ambon (Studi Kasus Pada Jurusan Teknik Industri) - Meiske D. Sopacua; D.B Paillin (Industrial Engineering Study Program, Pattimura University, 2015)
Scheduling is an important process in courses that established by filling numbers of component like major, lecturer, class and semester in timeslot, consisting of time and room. Scheduling systems of Engineering Faculty of Pattimura University perform manually that are not effective and efficient yet and might not be used for a long-term. Integer linear programming is a method to modeling scheduling problems with various obstacles that fitted to university needs. The aims of research are to formulate obstacles functions, objective function, optimal solution and sensitivity analysis of integer linear programming; and to obtain the best courses schedule using integer linear programming method. The result shows that obstacles functions could be formulated for getting an optimal solution. There is not a clashed schedule among lecturers who teaches more than one course.